Intertemporal budget policies and macroeconomic adjustment in a small open economy - Walter H. Fisher; Marcelo Bianconi (Institute for Advanced Studies (IHS), 2001)
This paper analyzes the role of nominal assets in ranking intertemporal budget policies in a growing open economy. The budget policies are ranked in terms of the public's intertemporal stock of tax liabilities. Our main result is that, in a small open economy, the valuation of private and public assets is in terms of the exogenous foreign price level under purchasing power parity. This constraint limits the scope of government to influence the real value of assets using fiscal and monetary policy shocks.
Keywords: E5; E6; F4; 330; government budget; taxation; nominal assets; current account; Finanzpolitik; Steuerpolitik; Neue Wachstumstheorie; Laffer-Kurve; Kleines-offenes-Land; Leistungsbilanz; Zahlungsbilanzungleichgewicht; Intertemporales Gleichgewicht; Theorie